Schaechter's mechanisms of microbial disease - Engleberg, N. Cary; DiRita, Victor J; Dermody, Terence (Kluwer, Lippincott Williams & Wilkins, 2013)
\"Schaechter\'s Mechanisms of Microbial Disease\" provides students with a thorough understanding of microbial agents and the pathophysiology of microbial diseases. The text is universally praised for \"telling the story of a pathogen\" in an engaging way, facilitating learning and recall by emphasizing unifying principles and paradigms, rather than forcing students to memorize isolated facts by rote. The table of contents is uniquely organized by microbial class and by organ system, making it equally at home in traditional and case-based curricula. Case studies with problem-solving questions give students insight into clinical applications of microbiology (an asset especially for problem-based learning curricula).
Keywords: Virus Diseases; infekční nemoci; Bacterial Infections and Mycoses; mikrobiologie, lékařská mikrobiologie; parazitární nemoci; infekční lékařství; virové nemoci; bakteriální infekce a mykózy; Parasitic Diseases; Communicable Diseases